International students’ satisfaction towards internet banking at International Islamic University Malaysia: a qualitative study - Uddin, Bashir; Haque, Ahasanul; Maulan, Suharni; Hasan, Syed (Research Publishing Academy (RPA), 2018)
This study explores International Students’ Satisfaction towards Internet Banking of Malaysia, applying a qualitative (phenomenology) approach, using the depth interview method. Semi organized open-finished interview has been conducted among seven international undergraduate and postgraduate students pursuing their degree from Kuala Lumpur city. The study finds that the present condition of online banking has not yet achieved flawlessness because of a few reasons like absence of security, absence of accessible data, unnecessary exchange time and so on. To address these reasons, financiers ought to prepare up their staff to administer web based banking offices to clients all the more productively. Continuing advancing new thoughts and arrangements to make web banking more appealing to clients can likewise be conceivable arrangements. Aside from that, clients ought to be given vital rules by bank staff on the most proficient method to keep their records, passwords and other secret things from getting hacked. Bank authorities may likewise run battles to make individuals careful of digital traps and deceitful online allurements.